Concurrent cisplatin or cetuximab with radiotherapy in patients with locally advanced head and neck squamous cell carcinoma: A meta-analysis. Issue 36 (4th September 2020) - Tang, Wen-Hua; Sun, Wei; Long, Guo-Xian
Abstract: Background: Concurrent cisplatin with radiotherapy (CRT) or concurrent cetuximab with radiotherapy (BRT) improves outcomes in locally advanced head and neck squamous cell carcinoma (HNSCC) compared with radiotherapy alone. Nevertheless, a detailed comparison between CRT and BRT in locally advanced HNSCC is required due to inconclusive results. Methods: A comprehensive literature search was conducted on PubMed, Web of Science, Cochrane databases, and EMBASE. Studies that evaluated CRT vs BRT in locally advanced HNSCC were included. The primary outcome that was overall survival (OS), whereas the secondary outcomes were progression-free survival (PFS), locoregional control (LRC), and distant metastasis-free survival (DMFS). Pooled hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs) were used to evaluate prognosis. All the analyses were performed using Stata Statistical Software 12.0. Results: Twenty-three studies, with a total of 8701 patients, were considered eligible and included in this meta-analysis. Our results revealed that patients treated with CRT had longer OS (HR = 0.51, 95%CI, 0.41–0.64, P < .001), PFS (HR = 0.37, 95%CI, 0.23–0.60, P < .001), LRC (HR = 0.46, 95%CI, 0.37–0.57, P < .001), and DMFS (HR = 0.56, 95%CI, 0.40–0.77, P < .001) than those treated with BRT. Furthermore, the results of the subgroup analyses were consistent with the primary analysis. Conclusions: CRT has a better OS, PFS, LRC, and DMFS than BRT in locally advanced HNSCC, and should be the preferred treatment for patients with the disease. Abstract : Supplemental Digital Content is available in the text